Anti-Drug Antibodies in Patients with Inflammatory Bowel Diseases Treated with Biosimilar Infliximab: A Prospective Cohort Study - Anna Pękala (Journal of Clinical Medicine, 2021)
Reports of the prevalence of antibodies to infliximab (anti-drug antibodies, ADA) are inconsistent due in part to the various assay formats used to monitor immunogenicity in the clinic and under clinical trial settings. This study aimed to determine the frequency of ADA in patients with inflammatory bowel disease (IBD) during induction and maintenance therapy with biosimilar infliximab (CT-P13) using the ELISA (enzyme-linked immunosorbent assay) method. In this prospective single-center study, we analyzed the incidence of ADA and the relationship between the presence of ADA and the following variables: gender, type of disease, immunosuppressive therapy used, and duration of treatment. A total of 84 patients with IBD received CT-P13 and were followed up for an average of 7 months. We found ADA in 50% of the patients with undetectable levels of the drug. The percentage of persons with antibodies detected during induction treatment was 11.3% compared to 9.6% during maintenance therapy. The analysis showed no relationship between response to treatment and antibody titers (p = 0.381). The study showed a statistically significant relationship between undetectable levels of CT-P13 and the presence of ADA at week 6 of therapy (i.e., ADA were detected in all the patients with undetectable levels of CT-P13). Patients with IBD and undetectable levels of CT-P13 before administration of the third induction dose were at high risk of the presence of anti-drug antibodies as well as primary non-response.